Peranan Pemerintah Dalam Mendorong Pertumbuhan Bank Syariah - Ishak Trianda (Sekolah Tinggi Manajemen Transportasi (STMT Malahayati Jakarta), 2024)
The Indonesian government as the driving force of national development. It is time to plan ahead to make Indonesia the center of the world's sharia economy. For that, it is necessary to accelerate the competitiveness of the national sharia economic industry. Starting with preparing a significant budget for socialization of supporting devices that make the rise and development of the sharia economy, especially sharia banking. Among them are preparing reliable human resources, it is estimated that in the future it will require 200 thousand new workers for sharia finance and banking, preparing a socialization budget for around 85% of the Indonesian population who are Muslim (240 million people) prospective users and beneficiaries of the sharia banking financial industry in the country. Including all Islamic boarding schools in 33 provinces of Indonesia (25 thousand Islamic boarding schools), 3.7 million students and a number of sharia micro business groups and BMT. It is hoped that it will later become a pillar of national development in order to be able to build a strong economic foundation, regulations, healthy industrial competition, modern industrial players, appropriate technology so as to support industrial efficiency. So that in time Indonesia will become the driving force of the world's sharia economy, surpassing Saudi Arabia, Iran and Malaysia. It is very possible, because currently the development of Indonesia's sharia economy continues to grow to 40% each year compared to conventional economic growth of only 19%. Even now Indonesia can be called a country with the largest sharia financial industry in the world because it has more than 20 thousand sharia cooperatives and Balai Mandiri Syariah Terpadu.